Research on Ratchaburi Local Fabric for Design Glass Tile for Decoration to Promote Identities Perception - Krairos, Chanon (Journal of the Thai Ceramic Society, 2025)
“Research on Ratchaburi Local Fabric for Design Glass Tile for Decoration to Promote Identities Perception” aims to 1) collecting and analyzing the properties, characteristics, and identities of local fabrics 2) to design works of art and crafts that promote the identity of Ratchaburi 3) to design works of art and crafts that promote the identity of Ratchaburi and 4) to use the design for the foundation of the development and occupation of the people of Ratchaburi. The researcher has studied concepts, theories, artistic styles, wisdom, culture and concept of image relationships in aesthetic design. Relationship of free space to applicated in design. Including reviewing related policy plans. After that, the researcher produced a data collection tool. To analyze the attitude and behavior of area users. Before use it to create a prototype glasses sheet for decoration in a various type, size, and design more than 20 works.